Analysis of the Influence of Entrepreneurial Orientation on Internasional Business Networking and Competitive Advantage, and Its Impact on the Marketing Performance of SMEs (A Study on SMEs in Kampung Embong Arab, Malang City) - Rijal, Muhammad Saifur; Sudarmiatin; Bidin, Rosmiza (Asian Journal of Management Analytics, 2024)
This study aims to analyze the influence of entrepreneurial orientation on business networking and Competitive Advantage and its impact on the export-import performance of Micro, Small, and Medium Enterprises (MSMEs) in the Arab Embong Village, Malang City. A survey method was employed to collect data from MSMEs operating in the village. Hypothesis testing was conducted using multiple regression analysis. The results show that entrepreneurial orientation has a significant influence on the formation of business networks. Furthermore, it was found that business networking has a positive and significant impact on the export-import performance of MSMEs. The implications of these findings underscore the importance of developing entrepreneurial orientation and fostering business networking for MSMEs to enhance their export-import performance. Therefore, it is recommended that the government and relevant institutions provide support and guidance to MSMEs in developing entrepreneurial skills and expanding their business networks.